PEMBAGIAN AL-KINAYAH DAN CONTOHNYA (AL-KINAYAH DALAM AL-QUR’AN) - Yudia Audriva; Anisyah Khoiroh Rangkuti (Jurnal Akademika Kajian Ilmu-Ilmu Sosial, Humaniora Dan Agama, 2026)
This study aims to analyze the concept, structure, and variants of kināyahas a rhetorical style in the Qur’an from the perspective of ‘Ilm al-Balāghah, particularly ‘Ilm al-Bayān. Using a qualitative descriptive-analytical method with a stylistic-balāghah approach, this study explores Qur’anic verses containing kināyahexpressions to identify their literal and figurative meanings. The findings show that kināyahhas two fundamental elements: al-lafẓal-mukannā bih(the expression used to convey the implied meaning) and al-mukannā ‘anhu(the intended inner meaning). These elements create a bridge between literal and connotative meanings, reflecting the eloquence and subtlety of Arabic expression. The study also classifies kināyahinto three main forms: kināyah ‘an aṣ-ṣifah(metonymy of an attribute), kināyah ‘an al-mawṣūf(metonymy of a described object), and kināyah ‘an an-nisbah(metonymy of relationship). Each variant serves to beautify expression, maintain linguistic politeness, and convey profound moral and spiritual messages. Therefore, kināyahis not merely a rhetorical ornament but also a theological and pedagogical medium that integrates aesthetic form with divine meaning.